2013
DOI: 10.3732/ajb.1300238
|View full text |Cite
|
Sign up to set email alerts
|

Predispersal seed predation is higher in a rare species than in its widespread sympatric congeners (Astragalus, Fabaceae)

Abstract: Our results support the hypothesis that a rare plant is more susceptible to seed predators than two common, sympatric congeners. Seed predator reduction is a promising management tool to increase seed-set, recruitment, and survival of the rare species. Further studies that compare rare-common, sympatric congeners are greatly needed to broadly evaluate the hypothesis concerning rarity and susceptibility to seed predators and to inform conservation plans for rare species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 50 publications
2
35
0
Order By: Relevance
“…Just as pollen limitation commonly constrains seed production, so too does pre-dispersal seed predation (Brody, 1991;Ehrlén, Käck, & Ågren, 2002;Leimu, Syrjanen, Ehrlén, & Lehtila, 2002;Louda, 1982;Weppler & Stoecklin, 2006). Perhaps due to their relatively large seeds, Astragalus species often suffer substantial pre-dispersal seed loss to insects, ranging from roughly 5% to 78% (Boe & Johnson, 2008;Combs, Lambert, & Reichard, 2013;Combs, Reichard, Groom, Wilderman, & Camp, 2011;Green, 1976;Jordano, Haeger, & Rodriguez, 1990;Kaye, 1999;Lesica, 1995;Platt, Hill, & Clark, 1974). In keeping with a prior observational study of A. utahensis (Green, 1976), we found that pre-dispersal seed predation strongly impacted seed production in this species.…”
Section: That Visitmentioning
confidence: 99%
“…Just as pollen limitation commonly constrains seed production, so too does pre-dispersal seed predation (Brody, 1991;Ehrlén, Käck, & Ågren, 2002;Leimu, Syrjanen, Ehrlén, & Lehtila, 2002;Louda, 1982;Weppler & Stoecklin, 2006). Perhaps due to their relatively large seeds, Astragalus species often suffer substantial pre-dispersal seed loss to insects, ranging from roughly 5% to 78% (Boe & Johnson, 2008;Combs, Lambert, & Reichard, 2013;Combs, Reichard, Groom, Wilderman, & Camp, 2011;Green, 1976;Jordano, Haeger, & Rodriguez, 1990;Kaye, 1999;Lesica, 1995;Platt, Hill, & Clark, 1974). In keeping with a prior observational study of A. utahensis (Green, 1976), we found that pre-dispersal seed predation strongly impacted seed production in this species.…”
Section: That Visitmentioning
confidence: 99%
“…Nevertheless, we presently lack the data to assess this prediction. These should be research priorities for the near future, as we know remarkably little about the phylogenetic distribution of traits related to chronic rarity (Kunin & Gaston 1993;Ancheta & Heard 2011;Combs et al 2013), much less the distribution of chronic rarity across the major physical realms of life, especially in highly diverse communities where there must be many rare species.…”
Section: Introductionmentioning
confidence: 99%
“…The use of demographic comparisons of related rare and common taxa is an established method for examining factors regulating rare plant populations (Karron, 1987;Walck et al, 1999). This method has been used to compare functional traits (Hand et al, 2017), seed production and germination (Brown et al, 2003), reproductive and ecophysiological attributes (Osunkoya and Swanborough, 2001), responses to herbivory and invasive species removal (Leege et al, 2010), predispersal seed predation (Combs et al, 2011(Combs et al, , 2013, and the effects of invasive competitors (Combs et al, 2011) for rare and common taxa. In these studies, many of which compare endemic and widespread congeners, the noted demographic differences highlight the challenges that rare species face.…”
mentioning
confidence: 99%
“…Such a comparative framework can provide a better understanding of species characterized by narrow endemism, those that occur in one or a few populations and thus are confined to a single domain or a few localities (Kruckeberg and Rabinowitz, 1985). Furthermore, the use of a framework that examines rare-common differences in sympatric congeneric populations may be especially insightful because confounding factors such as differences in phylogeny, ecology, and local environmental factors can be controlled or reduced (Combs et al, 2013). Despite the applicability of this method, few studies have directly tested whether the process of seed dispersal differs for rare and common species (Pirie et al, 2000).…”
mentioning
confidence: 99%